On paper the everything of its two-thousand-year history - Basbanes, Nicholas A. 1943- (Alfred A. Knopf, 2013)
"A consideration of all things paper--the invention that revolutionized human civilization; its thousand-fold uses (and misuses); its sweeping influence on society; its makers, shapers, collectors, and pulpers--by the admired cultural historian."--Book jacket.